2014
DOI: 10.1007/s12013-014-9973-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ezetimibe on Endothelial Progenitor Cells and Microparticles in High-Risk Patients

Abstract: Imbalance on endothelial turnover can predict cardiovascular outcomes. We aimed at evaluating the effects of lipid-modifying therapies on circulating endothelial progenitor cells (EPCs), endothelial microparticles (EMPs), and platelet microparticles (PMPs) in high cardiovascular risk subjects with elevated C-reactive protein (CRP). Sixty-three individuals with coronary heart disease (CHD) or CHD risk equivalent on stable statin therapy, with LDL-cholesterol <100 mg/dL and CRP ≥ 2.0 mg/L were selected. After a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…92 . A lack of effect on microparticles and endothelial progenitor cells by ezetimibe treatment was reported also in patients at high-risk for coronary heart disease 93 . The Simvastatin and Ezetimibe in Aortic Stenosis (SEAS) trial has been designed to assess the effects of long-term (4.3 years) treatment with ezetimibe+simvastatin in patients with asymptomatic, mild-to-moderate aortic-valve stenosis 96 (Table 2).…”
Section: Inhibition Of Npc1l1 By Ezetimibe and Inflammationmentioning
confidence: 88%
“…92 . A lack of effect on microparticles and endothelial progenitor cells by ezetimibe treatment was reported also in patients at high-risk for coronary heart disease 93 . The Simvastatin and Ezetimibe in Aortic Stenosis (SEAS) trial has been designed to assess the effects of long-term (4.3 years) treatment with ezetimibe+simvastatin in patients with asymptomatic, mild-to-moderate aortic-valve stenosis 96 (Table 2).…”
Section: Inhibition Of Npc1l1 By Ezetimibe and Inflammationmentioning
confidence: 88%
“…It has been reported on the basis of bulk analysis that the total amounts of EVs of different sizes and origins are elevated in patients with higher cardiovascular risk scores [11], endothelial dysfunction [3436], ischemic stroke [12,37], stable atherosclerotic plaques [13,38], and acute coronary syndromes [15,21,22,3943]. Moreover, it has been shown that EV levels correlate with clinical outcomes in patients with coronary artery disease [44,45] and are reduced with statin therapy [46,47]. …”
Section: Discussionmentioning
confidence: 99%
“…However, some authors did not observe such effect of statins [96,97], and, as discussed in the 2019 ESC/EAS Guidelines for the management of dyslipidemias, the clinical relevance of the pleiotropic effects of statins remains clinically unproven [98], and thus may be object of future research.…”
Section: Pharmacological Treatment Of Dyslipidemia and Circulating MVmentioning
confidence: 97%